The Need for Social Ethics in Interdisciplinary Environmental Science Graduate Programs: Results from a Nation-Wide Survey in the United States. - Hall, Troy; Engebretson, Jesse; O'Rourke, Michael; Piso, Zach; Whyte, Kyle; Valles, Sean (Science & Engineering Ethics, 2017)
Professionals in environmental fields engage with complex problems that involve stakeholders with different values, different forms of knowledge, and contentious decisions. There is increasing recognition of the need to train graduate students in interdisciplinary environmental science programs (IESPs) in these issues, which we refer to as 'social ethics.' A literature review revealed topics and skills that should be included in such training, as well as potential challenges and barriers. From this review, we developed an online survey, which we administered to faculty from 81 United States colleges and universities offering IESPs (480 surveys were completed). Respondents overwhelmingly agreed that IESPs should address values in applying science to policy and management decisions. They also agreed that programs should engage students with issues related to norms of scientific practice. Agreement was slightly less strong that IESPs should train students in skills related to managing value conflicts among different stakeholders. The primary challenges to incorporating social ethics into the curriculum were related to the lack of materials and expertise for delivery, though challenges such as ethics being marginalized in relation to environmental science content were also prominent. Challenges related to students' interest in ethics were considered less problematic. Respondents believed that social ethics are most effectively delivered when incorporated into existing courses, and they preferred case studies or problem-based learning for delivery. Student competence is generally not assessed, and respondents recognized a need for both curricular materials and assessment tools.